Determinants of Willingness-to-Pay A Premium Price for Integrated Pest Management Produced Fruits and Vegetables in Trinidad - G Kathiravan; Saravanakumar Duraisamy; Ataharul Chowdhury; Wayne Ganpat (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2020)
Overuse of pesticide in crop production poses enormous challenges to the health of farm families, consumers, and the environment. Integrated Pest Management (IPM) is an ecosystem approach to crop production that combines different management strategies and practices to grow healthy crops and minimize the use of pesticides. As a result of increasing awareness, education and per capita income, there is an increasing concern for food safety and demand for safe products among consumers of high-income countries. Consequently, this study was conducted among 266 randomly surveyed consumers of an affluent Caribbean country, Trinidad to ascertain the factors influencing consumers Willingness-To-Pay (WTP) a premium price for IPM grown-fruits and vegetables. The consumers responses for the dichotomous question, Would you be Willing to Pay an additional cost of 10% for the IPM produces from the current market prices? were analysed using Binary logit regression model. Results indicated that females ageing over 26 years and having children, those with higher annual income and higher level of education were all most likely to pay a premium to obtain IPM grown fruits and vegetables. Willingness-to-purchase IPM produce was found to increase with income, education and age. The findings of this study are promising to those developing marketing strategies, besides enabling the producers to understand that producing fruits and vegetables through IPM would fetch them premium.